In a younger voice doing child-centered qualitative research - Clark, Cindy Dell. (Oxford : Oxford University Press, 2011)
Adults were once children, yet a generational gap can present itself when grown-ups seek to know children's lives, in research. This work discloses how qualitative research, tailored to be child-centered, can shrink the gap of generational unintelligibility.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Child development -- Research -- Methodology; Qualitative research